Wanprestasi Perjanjian Kerja Sama Pembangunan Ruko Ditinjau Dari Teori Perjanjian - Hendra, Hendra; Prihardiati, RR. Lyia Aina (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Default agreement we often find in everyday life. One of the interesting agreements to examine is that the shophouse construction agreement has been sued in court and received a court decision number 6/Pdt.G/2019/PN.DPK. The formulation of the problem in this research is How do the judges consider the decision number 6/Pdt.G/2019/PN.DPK in terms of agreement theory? and Is the decision 6/Pdt.G/2019/PN.DPK in accordance with the theory and concept of default? The research method used is normative juridical with primary, secondary and tertiary legal materials. The conclusion obtained is that the considerations in decision number 6/Pdt.G/2019/PN.DPK in terms of agreement theory are correct, because the judge acknowledged and declared the agreement valid. Then Decision 6/Pdt.G/2019/PN.DPK was not appropriate with the theory and concept of default. because he promised to be ratified by a judge who deserved to complete his achievements was the plaintiff, not the defendant.